Nicotinic Acetylcholine Receptor α7 Subunit Mediates Migration of Vascular Smooth Muscle Cells Toward Nicotine - Sheng Li; Tiejun Zhao; Hong Xin; Li-Hong Ye; Xiaodong Zhang; Hideyuki Tanaka; Akio Nakamura; Kazuhiro Kohama (Elsevier, 2004)
GbaSM-4 cells, vascular smooth muscle cells (VSMCs) derived from brain basilar arteries, were shown to migrate toward d-nicotine by augmenting the actin cytoskeleton in their cell bodies and lamellipodia, and expression of nicotinic acetylcholine receptor (α7-nAChR) was detected in GbaSM-4 cells. Their chemotaxis was antagonized by an α7-nAChR antagonist of methyllycaconitine. It was also antagonized by inhibiting myosin light chain (MLC) kinase and by down-regulating MLC kinase. However, the changes in MLC phosphorylation were not associated with the nicotine treatment, suggesting the involvement of non-kinase activity of MLC kinase as reviewed by Gao et al. (IUBMB Life. 2001;51:337). This plot may work to induce arteriosclerosis during cigarette smoking. Keywords:: d-nicotine, α7 subtype of nicotinic acetylcholine receptor, migration of vascular smooth muscle